TEORI GENDER DALAM MEWUJUDKAN KESETARAAN: MENGGAGAS FIKIH BARU (Ahkam: Jurnal Hukum Islam, 2017)
Gender Theory in Achieving Equality of Fighting New Fiqh actually ideally does not differentiate between men and women, let alone discriminate against women. Even bringing welfare and mercy to the whole of nature, Islam places the elevation and position of women as proof of its virtue. The gender bias is essentially derived from three basic assumptions about religious beliefs; 1) dogmatic assumptions that explicitly place women as complementary, 2) the matrealistic outlook, the ideologyb of the pre-Islamic Meccan society which despises the role of women in the production process. Initiating the new fiqh, it is hoped that there will be more humane and fairer views. Women have full access to political, economic, social and intellectual participation and are respected as men.Keywords: Gender, Equality, New Jurisprudence